The exploration of Al-Sarihi’s temptation of the name: A biography of coffee and the discourse of prohibition from cultural discourse analysis - Alhosami, Abdulhameed Saif; Alkam, Sabha Ahmad (International Journal of Innovative Research and Scientific Studies, 2025)
This article aims to reconsider Al-Sarihi’s Temptation of the Name: A Biography of Coffee and the Discourse of Prohibition from a cultural discourse analysis. The analytical approach is a scientific method used in studying the contents of literary research, which shows a strong relationship between this approach and the contents of literary research. The findings demonstrate that Al-Sarihi’s Temptation of the Name: A Biography of Coffee and the Discourse of Prohibition has a specific aim represented by reading the discourse in a profound and philosophical reading, which is embodied by drawing inspiration from the spirit of the Foucauldian reading of the discourse. Another key point is that the article concludes that the spirit of Foucauldian reading of discourse includes shifting its understanding of discourse and the mechanisms of deconstruction that seek to work in two mutually reinforcing approaches: the historical path of the phenomenon, investigating the roots of coffee, and the novels that monitored this on the one hand. One of the implications is reflected in conducting future studies of marginal cultural discourses based on the method of analyzing cultural discourse with its methodological procedures, especially those discourses that have not received an in-depth critical study.